2011
DOI: 10.1002/zaac.201100357
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures and Stabilities of γ‐ and γ′‐Brass Phases in Pd2–xAuxZn11 (x = 0.2–0.8): Vacancies vs. Valence Electron Concentration

Abstract: To probe the effect of valence electron concentration (vec or e -/atom) on γ-Pd 2+x Zn 11-x phases a series of compounds Pd 2-x Au x Zn 11 (x = 0.3-0.8; e -/atom = 1.70-1.75) was synthesized and structurally characterized. The gold-substituted γ-brass type phase was observed for x Յ 0.3, having a refined composition of Pd 1.93 Au 0.27(1) Zn 10.80(1) (space group I43m; a = 9.0953 (2) Å). Further addition of gold (0.4 Յ x Յ 0.8) leads to a 2 ϫ 2 ϫ 2 superstructure of the γ-brass type phase (denoted as the γЈ-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…We demonstrated that partial replacement of the sp metal Al for Zn in γ‐Pd 2– x Zn 11+ x leads to either a ternary γ‐brass or a 2 × 2 × 2 superstructure of the γ‐brass structure 19c. Moreover, similar results can also be achieved by replacing some Pd atoms with monovalent Au to obtain γ‐Pd 2– x Au x Zn 11 ( x = 0.2–0.8) phases 19a. On further synthetic explorations to understand the effect vec on γ‐Pd 2– x Zn 11+ x with Mg substitution, we observed formation of Laves phases and other complex structures related to Mg 51 Zn 20 20 instead of γ‐brass type phases.…”
Section: Introductionmentioning
confidence: 63%
“…We demonstrated that partial replacement of the sp metal Al for Zn in γ‐Pd 2– x Zn 11+ x leads to either a ternary γ‐brass or a 2 × 2 × 2 superstructure of the γ‐brass structure 19c. Moreover, similar results can also be achieved by replacing some Pd atoms with monovalent Au to obtain γ‐Pd 2– x Au x Zn 11 ( x = 0.2–0.8) phases 19a. On further synthetic explorations to understand the effect vec on γ‐Pd 2– x Zn 11+ x with Mg substitution, we observed formation of Laves phases and other complex structures related to Mg 51 Zn 20 20 instead of γ‐brass type phases.…”
Section: Introductionmentioning
confidence: 63%
“…Most often, this involves atoms of two different elements randomly distributed over the same crystallographic sites. Substitutions of larger atom groups can arise as well, such as disorder in the coordination environment of an atom, leading to the possibility of several different polyhedra fitting into the same space. , In this article, we began examining how such substitution can be anticipated from the CP scheme of an idealized, unsubstituted parent structure, drawing specific examples from the Y–Co system. We considered two cases: the partial replacement of Y atoms with Co 2 dumbbells in YCo 5 to create the Th 2 Zn 17 -type compound Y 2 Co 17 , and the elemental site preferences in Ru-substituted variants of Y 2 Co 17 .…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Similar behavior occurs in the Fe−Zn, 6 Ni−Zn, 7 Rh−Zn 8 and Pt−Zn systems. 9 Subsequent modification of vec values in γ-brass Pd−Zn phases by introducing a third element, e.g., substituting trivalent Al for divalent Zn or monovalent Au for zerovalent Pd (just valence s and p electrons are counted), 10−12 yielded cubic γ-brass and 2 × 2 × 2 cubic superstructures, designated as γ′ brass, in the Pd−Al−Zn 10,11 and Pd−Au−Zn 12 systems. These ternary γand γ′-brass phases exhibit directed mixed site occupancies as well as the presence of vacancies, both of which influence the vec of these phases to fall between 1.71 and 1.75 e − /a.…”
Section: ■ Introductionmentioning
confidence: 99%